Metabolism and Physiological Functions Adjustment of the Organism under Stress Influence - L. R. Kolesnikova; O. A. Makarova; L. V. Natyaganova; M. I. Dolgikh; L. I. Korytov (Acta Biomedica Scientifica, 2019)
Stress reaction of the organism is a process occurring at the cellular, tissue and systemic levels. The organism responds to any adverse effect with a multi-level reaction, which causes the development of stress and, as a result, adaptation. The damaging effect is due to the excessive strengthening of another adaptive effect – lipotropic, that increases the activity of phospholipases and the intensity of free radical oxidation of lipids through the catecholamines and protein kinases. The changes in the immune system during the adaptation stage are to maintain antigenic homeostasis of the internal environment of the organism due to lymphoid cells, lymphocytes and cytokines. Almost all cells with antigen representation function are capable to produce interleukins under certain conditions. The vascular system is a kind of an indicator of any pathological process, determining the state of regulatory and adaptive mechanisms, the features of the connective tissue matrix. Stress causes a restructuring of metabolism and physiological functions, which increases the organism’s resistance to acute death. Thus, the physiological meaning of the stress reaction is the emergency mobilization of energy and structural resources of the organism and the creation of positive background for the implementation of reactions, aimed at maintaining homeostasis in extreme situations.